Fabrication of three-dimensional metal-graphene network phase change composite for high thermal conductivity and suppressed subcooling phenomena. (1st October 2017) - Heu, Chang Sung; Kim, Sun Woo; Lee, Kwan-Soo; Kim, Dong Rip
Highlights: Three-dimensional metal-graphene network phase change composite was fabricated. Thermal conductivity of phase change composite significantly increased. Subcooling phenomena of phase change material was significantly suppressed. Heat of fusion of phase change composite was minimally sacrificed. Phase change composite was stable under repeated thermal cycles. Abstract: We report the fabrication of a three-dimensional (3D) metal-graphene network-based phase change composite with a tunable size of individual phase change materials under the same amount of metal contents. Mixing the granules of phase change material with metal paste and subsequent hot pressing effectively forms 3D metal networks among phase change materials with a minimal inclusion of metal. Specifically, the formation of a 3D silver network with 6 volume percentages among pure erythritol increases the thermal conductivities of pure erythritol by 2.7-fold, while achieving a heat capacity that is comparable to that of pure erythritol. Decreasing the size of the individual erythritol part with the same metal content significantly suppresses the subcooling phenomena of erythritol by 24 °C due to the effectively increased interfacial surface areas for active heterogeneous nucleation. The addition of graphene sheets between the erythritol granules and 3D metal network further enhances the thermal conductivities of phase change composites by 4.7-fold compared to those of pure erythritol. Finally, the stable operation of the 3D metal or metal-graphene network-based phase change composite during repeated melting and solidification cycling revealed the good structural integrity of the fabricated phase change composite.